Transgenic Plants - Zerbini, F.M.; Silva, F.N.D.; Urquiza, G.P.C.; Basso, M.F.
Humankind has genetically manipulated plant crops for many years through conventional breeding. Until recently, breeding was the only way to introduce phenotypic characteristics of interest, which are determined by genes, to an individual plant or species. The desired phenotypic traits are transferred to the progeny through breeding and selection. However, such conventional methods of genetic manipulation have some limitations, including the sexual barrier between species, phylogenetic isolation barriers between and within genetic groups, a reduced gene pool, and linkage drag. All of these drawbacks are in addition to the lengthy time usually required for desirable traits to be transferred.
Keywords: AGROBACTERIUM TUMEFACIENS; CULTIVAR; MICROPARTICLES; MRNA; RESTRICTION ENZYMES; T-DNA